Salvianolic acid B attenuates tubulointerstitial fibrosis by inhibiting EZH2 to regulate the PTEN/Akt pathway - Pinglan Lin; Furong Qiu; Ming Wu; Lin Xu; Di Huang; Chen Wang; Xuejun Yang; Chaoyang Ye (Pharmaceutical Biology, 2023)
AbstractContext Salvianolic acid B (SAB) can alleviate renal fibrosis and improve the renal function.Objective To investigate the effect of SAB on renal tubulointerstitial fibrosis and explore its underlying mechanisms.Materials and methods Male C57 mice were subjected to unilateral ureteric obstruction (UUO) and aristolochic acid nephropathy (AAN) for renal fibrosis indication. Vehicle or SAB (10 mg/kg/d, i.p.) were given consecutively for 2 weeks in UUO mice while 4 weeks in AAN mice. The serum creatinine (Scr) and blood urine nitrogen (BUN) were measured. Masson’s trichrome staining and the fibrotic markers (FN and α-SMA) were used to evaluate renal fibrosis. NRK-49F cells exposed to 2.5 ng/mL TGF-β were treated with SAB in the presence or absence of 20 μM 3-DZNep, an inhibitor of EZH2. The protein expression of EZH2, H3k27me3 and PTEN/Akt signaling pathway in renal tissue and NRK-49F cells were measured by Western blots.Results SAB significantly improved the levels of Scr by 24.3% and BUN by 35.7% in AAN mice. SAB reduced renal interstitial collagen deposition by 34.7% in UUO mice and 72.8% in AAN mice. Both in vivo and in vitro studies demonstrated that SAB suppressed the expression of FN and α-SMA, increased PTEN and decreased the phosphorylation of Akt, which were correlated with the down-regulation of EZH2 and H3k27me3. The inhibition of EZH2 attenuated the anti-fibrotic effects of SAB in NRK-49Fs.Conclusion SAB might have therapeutic potential on renal fibrosis of CKD through inhibiting EZH2, which encourages further clinical trials.